Uji Ketersediaan Hayati Tablet Parasetamol dan Tablet Teofilin pada Kelinci - DJOKO WAHYONO; ARIEF RAHMAN HAKIM (Fakultas Farmasi Universitas Pancasila, 2009)
The objective of this research is to evaluate the bioavailability of paracetamol tablet to Panadol and theophyllin tablet to Bronsolvan in rabbits. The study Was conducted employing a same subject design using male rabbits which were divided into 2 groups (5 rabbits for each group). The group I was given a single oral antipyretic tablet (paracetamol 500 mg) and the group H was given a single oral antiasthmatic tablet (theophyllin 130 mg). After Wash out period, the group I Was given asingle oral Panadol tablet (paracetamol 500 mg) and the group ll Was given a single oral Bronsolvan tablet (theophyllin 150 mg). Serial blood samples were taken at various interval time for HPLC analysis of unchanged form of paracetamol and theophyllin in blood. Based on the data of the concentration over the time, the pharmacokinetic parameters (Cmaks, tmaks, and AUC0- ̴ ) were determined and compared using statistic analysis paired t test with 95% degree of comidence. The results indicated that the bioavailability of antipyretic and antiasthmatic tablet is not significantly difference to the respective controls (P>0,05).